Birdwatching in Peru: 1963-2006 - Lüthi, Hansjakob (2011)
In this paper we present the observations and sightings of birds carried out in 24 departments of Peru between 1963 and 2006. Information on the locations and altitudes is discussed for a total of 319 species from 62 families, and for some species are reported behavior, phenology and songs. 83% of the observations were made between 1963 and 1976 and 37% correspond to observations made in the Department of Lima.